Prevalence of dietary supplement use by gym members in Portugal and associated factors - João Ruano; Vitor Hugo Teixeira (Taylor & Francis Group, 2020)
Background Although there seems to be an increasing interest in the use of dietary supplements in those who exercise recreationally and want to improve body composition, there is little published data regarding gym users and dietary supplement use. Methods This cross-sectional study describes the prevalence and type of supplements used by gyms members, the reasons for using them and the information source using a self-administered online questionnaire. Results Of the 459 participants (301 females) who answered the survey, 43.8% reported using dietary supplements. Users were more likely men (62.7% vs. 33.9%, p < 0.05), younger (32 ± 9 vs. 34 ± 11 years, p < 0.05) and trained more hours per week (6 ± 3 vs 4 ± 3 h, p < 0.05) than non-users. The most consumed supplements were proteins (80.1%), multivitamins and/or minerals (38.3%), sport bars (37.3%), branched-chain amino acids (BCAA's) (36.8%) and n-3 fatty acids (35.5%). Men consumed more arginine, BCAA's, creatine, glutamine, β-hydroxy-β-methylbutyrate (HMB), proteins, β-alanine, taurine, multivitamin/minerals, and carbohydrate supplements (p < 0.05). The most commonly cited reasons for the use of supplements were gaining muscle (55.7%), accelerating recovery (52.7%) and improving performance (47.3%). Men have more often referred increase strength, increase resistance, gain muscle mass, accelerate recovery and improve performance as reasons to use supplements than women (p < 0.05). Those who mentioned muscle gain as a reason were younger than those who did not (30.4 years vs. 33.7 years, p < 0.05). The sources of information most mentioned were registered dietitians (23.1%), internet (22.2%) and him/herself (16.6%). The majority (> 70%) of participants declared being well or very well informed about supplements, while only a minority (4%) felt very poorly or poorly informed. Most individuals purchased dietary supplements from the internet (56.2%) and supplement/health food stores (43.4%). Conclusion This study concluded that gyms users are large consumers of dietary supplements, and are more likely to be men, young, use protein powders, aiming to increase muscle mass, obtain information from registered dietitians, consider themselves well informed and buy supplements online.